The role of infection at COPD exacerbations - Wedzicha, Wisia (Henry Stewart Talks, 2013)
Roles of viral and bacterial infections at exacerbations of COPD, Airway bacteria, RCT of antibiotic therapy, Sputum characteristics, Bacterial eradication & inflammation, Bacterial strain change, Lung microbiome in smoker vs. COPD, Plasma fibrinogen at exacerbation, Exacerbation frequency & common cold in COPD, Rhinovirus, Eosinophilic markers of viral exacerbations, Lower lobe bronchiectasis, Doxycycline vs. placebo, Long term antibiotics, Patients with purulent/mucopurulent sputum – Macrolide studies, RSV infection in COPD